Optical spectra of CuO2 and matrix effect upon its structure: Low-Temperature Physics and Chemistry in Cryomatrice - Caspary, Nico; Savchenko, Elena V.; Thoma, Anton; Lammers, Andreas; Bondybey, Vladimir E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Optical absorption and laser induced fluorescence (LIF) spectra of CuO2 in solid matrices have beeninvestigated, and previous visible studies were extended into the infrared. Several new electronic states were observed and their vibrational frequencies determined. The matrix data are compared with the results of recent gas phase CuO2‾ photodetachment studies, and with ab initio calculations. We also discuss the unusually large matrix effects and medium-induced electronic and vibrational frequency shifts observed for CuO2.